2019
DOI: 10.4236/gep.2019.71006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Two-Layer Models for Velocity Profiles in Open-Channels with Submerged Vegetation

Abstract: For submerged vegetated flow, the velocity profile has two distinctive distributions in the vegetation layer in the lower region and the surface layer in the upper non-vegetated region. Based on a mixing-layer analogy, different analytical models have been proposed for the velocity profile in the two layers. This paper evaluates the four analytical models of Klopstra et al., Defina & Bixio, Yang et al. and Nepf against a wide range of independent experimental data available in the literature. To test the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Rigid submerged vegetation has been the subject of a large number of investigations [7,61,62,[73][74][75][76][77] and comparisons [78][79][80][81][82][83]. Some researchers provided the average velocity values in the two layers, while others derived the velocity distribution and the average values [7,73,74,76].…”
Section: Submerged Rigid Vegetationmentioning
confidence: 99%
“…Rigid submerged vegetation has been the subject of a large number of investigations [7,61,62,[73][74][75][76][77] and comparisons [78][79][80][81][82][83]. Some researchers provided the average velocity values in the two layers, while others derived the velocity distribution and the average values [7,73,74,76].…”
Section: Submerged Rigid Vegetationmentioning
confidence: 99%
“…In the evaluation of the above models and other models, Tang & Ali (2013) and Tang (2019a) showed that the predicted velocity distribution by the above mentioned models is acceptable only for certain experimental datasets, but they do not agree with other datasets. In addition, the predictions by these models show significant differences even for the same dataset.…”
Section: Introductionmentioning
confidence: 97%
“…Tsujimoto & Kitamur, 1990, Shimizu & Tsujimoto, 1994Nepf & Koch, 1999;Ghisalberti & Nepf, 2004;Kubrak, et al, 2008;Tang & Knight, 2009;Tang et al, 2010Tang et al, , 2011Nguyen, 2012;Hao et al, 2014). Many investigators have attempted to predict vertical velocity distribution based on semi-empiricism and/or analytical solution of the momentum equation with closure schemes, in which the modelling of eddy viscosity is to describe the turbulent stresses (Klopstra et al, 1997;Meijer & Van Velzen, 1999;Defina & Bixio, 2005;Baptist et al, 2007;Huai, et al, 2009Huai, et al, , 2014Yang & Choi, 2010;Dimitris & Panayotis, 2011;Nepf, 2012;Nikora et al, 2013;Tang, 2018aTang, , 2019aSingh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations